From the Wharf, Port of Spain, Trinidad - Briant (Davidson and Todd, [Trinidad and Tobago], 2011)
The postcard shows fishing boats anchored in the Port of Spain harbour, Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Harbors--Trinidad and Tobago; Waterfronts--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Fishing boats--Trinidad and Tobago; Shorelines--Trinidad and Tobago; Wharves--Trinidad and Tobago